2015
DOI: 10.1016/j.watres.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Legionella pneumophila MLVA-genotypes in a drinking water system

Abstract: 14Bacteria of the genus Legionella cause water-based infections, resulting in severe pneumonia. 15To improve our knowledge about Legionella spp. ecology, its prevalence and its relationships 16 with environmental factors were studied. Seasonal samples were taken from both water and 17 biofilm at seven sampling points of a small drinking water distribution system in Israel. 18Representative isolates were obtained from each sample and identified to the species level. L. water. This observation deserves further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
52
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 45 publications
5
52
1
Order By: Relevance
“…In a yearly survey, we (19) demonstrated that different sites along a water network were dominated by different genotypes (for more details, see Fig. 7 in the study by Rodriguez-Martinez et al [19] and Table 1 in the current article).…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…In a yearly survey, we (19) demonstrated that different sites along a water network were dominated by different genotypes (for more details, see Fig. 7 in the study by Rodriguez-Martinez et al [19] and Table 1 in the current article).…”
mentioning
confidence: 57%
“…Sites with the lowest temperature range (ϳ21°C) harbored Gt4 and had Legionella counts of up to 1 or 2 orders of magnitude higher than Legionella counts at the other sites. Gt15 was dominant at sites with high temperatures (45°C) but with lower Legionella counts than at the other sites (19). This effect of temperature on the survival, growth, and prevalence of the different genotypes at the different drinkingwater distribution sites (Table 1) deserves extensive investigation and was addressed in the present study.…”
mentioning
confidence: 79%
See 3 more Smart Citations